Plant Hormones Recent Advances, New Perspectives and Applications - Hano, Christophe (IntechOpen, 2022)
Plant hormones are among the most essential biochemicals found in plants. Since Charles and Francis Darwin identified auxin action, several plant hormones have been discovered. These small signaling molecules regulate not only developmental and growth activities, but also stress responses throughout the plant's life cycle. This book discusses recent advances, new perspectives, and applications of plant hormones. It is a useful resource for academics, scientists, students, and industry professionals.